Doppler assessment of fetal well-being – A rational approach - Niraj Kumar Dipak; Babit Kumar; Apoorva Reddy; Karnika Tiwari (Indian Journal of Child Health, 2021)
Doppler sonography provides insight into the uteroplacental and fetoplacental circulation non-invasively. It has important diagnostic implications in fetal growth restriction (FGR), monitoring of multiple pregnancies complicated by discordancy and placental vascular communications in twin-to-twin transfusion syndrome (TTTS), and fetal anemia; particularly, red blood cell isoimmunization in Rh-negative pregnancies. There is a sequence of changes in UA Doppler velocimetry whenever there is fetal compromise, that is, increased S/D ratio, centralization of flow (brain-sparing effect) followed by absent end-diastolic flow and finally reversed end-diastolic flow. When venous Doppler studies e.g., umbilical vein (UV), ductus venosus (DV), and inferior vena cava (IVC) Doppler also become abnormal, perinatal mortality and still birth increase manifold. Vertebroplacental ratio (VPR) is proved to be an alternative to cerebroplacental ratio (CPR) in fetal surveillance near term. DV flow assessment in the first trimester has a vital role in screening for chromosomal abnormalities and cardiac defects.